Principles of neural science (Appleton & Lange, 1998)
The cornerstone reference in the field of neuroscience that explains how the nerves, brain, and mind function. Clear emphasis on how behavior can be examined through the electrical activity of both individual neurons and systems of nerve cells. Current focus on molecular biology as a tool for probing the pathogenesis of many neurological diseases, including muscular dystrophy, Huntington disease, and certain forms of Alzheimer’s disease.